Modern Protestantism and positive law : the contours of a continental theological tradition - Shingleton, A. Bradley (Pickwick Publications, 2019)
The nature and role of positve law has largely been neglected in recent Protestant theology and social ethics. Modern Protestantism and Positive Law introduces and critically summarizes a tradition in Continental Protestant thought about human law, drawing on writings of Barth, Brunner, Ellul, Thielicke, Wolf, Pannenberg, Huber, and Kreß, many of which have not been translated into English. The book argues that law is an essential political and social institution within developed societies, one that is normative and dependent on an encompassing vision of justice but that also necessarily reflects the contemporary pluralism of those societies. Modern Protestantism and Positive Law argue that theological and ethical perspectives on positive law developed by Protestant thinkers have a place in feflection on positive law, provided they are conceived and expressed in a manner appropriately respectful of the diversity of contemporary opinion regarding the expression of religious perspectives in the public arena.